Characterization of the effects of binary probiotics and wolfberry dietary fiber on the quality of yogurt. (16th April 2023) - Fan, Xiankang; Shi, Zihang; Xu, Jue; Li, Chunwei; Li, Xiefei; Jiang, Xiaoxiao; Du, Lihui; Tu, Maolin; Zeng, Xiaoqun; Wu, Zhen; Pan, Daodong
Graphical abstract: Characterization of the effects of binary probiotics and WDF on the quality of yogurt. A simplified version of the experiment conducted in this study. Highlights: Compounds that improve yogurt quality in wolfberry dietary fiber are confirmed. Binary probiotics are more suitable for fermented wolfberry dietary fiber yogurt. The tyrosine metabolic pathway could enhance the growth of L. casei 56. Forty-six volatile flavor compounds were found in yogurt. Abstract: The effects of binary probiotics ( Lacticaseibacillus casei CGMCC1.5956 and Lactiplantibacillus plantarum subsp. plantarum CGMCC 1.5953) in conjunction with wolfberry dietary fiber (WDF) on yogurt quality were investigated in this study. d -fructose, β-d -glucose, 6-acetyl-d -glucose, and 1-ketose in WDF significantly improved syneresis, apparent viscosity, and elastic behavior of yogurt. Binary probiotics were more suitable for fermenting WDF yogurt than single probiotics, resulting in a higher viable count (9.39 lg (CFU/mL)) and unique flavor. Binary probiotics can promote the production of tyrosol by L. casei 56 through the tyrosine metabolic pathway, thereby enhancing the resistance of L. casei 56 and L. plantarum 53 to their environment and promoting growth. Pyridine, 2, 3, 4, 5-tetrahydro- and prenol might be responsible for the high odor scores in the sensory evaluation of WDF yogurt prepared using binary probiotics. In summary, combining binary probiotics and WDF can significantly improve yogurt quality and add value to the final product.